CHARACTERIZATION OF NATURAL ZEOLITE BY X-RAY DIFFRACTOMETER - Supandi Suminta (Jurnal Zeolit Indonesia, 2006)
An identification of framework mineral structure of natural zeolit Bayah, Lampung and Malang was carried out by Reitveld methods. X ray diffraction intensity of Natural zeolit was measured by an X-Ray Diffractometer (XRD). The refinement of Clinoptilolite and Mordenite phases have been carried out and the results of refinement show that in Bayah and Lampung were Clinoptilolite phase ( space group C2/m No.12, Bravais lattice is Base-Centered and crystal system is monoclinic) and lattice parameter are a = 17,69(2) Å, b = 17,92(1) Å dan c = 7,422(9) Å respectively (Bayah zeolite) and a = 17,69(2) Å, b = 17,92(1) Å dan c = 7,422(9) Å respectively (Lampung zeolite) and pore size are S10R = 10,685 Å dan S8R = 8,193 Å. While Malang zeolites phase (space group Cmcm No.63, Bravais lattice is Base Centered and crystal system is orthorombic) was Mordenite phase and the lattice parameter are a = 18,115(8) Å, b = 20,520(9) Å dan c = 7,515(2) Å. The pore size are S8R = 11,43 Å dan S12R = 7,730 Å. Material of natural zeolit from Bayah and Lampung have Cation Exchange Capasity (CEC) bigger than Malang (acording to results of the framework structure analysis).